Physical characteristics explain ball-carrying capability in sub-elite rugby union players - Hart, A. S.; Erskine, R. M.; Mclaughlin, T. J.; Clark, D. R. (Journal of Science in Sport and Exercise, 2023)
Purpose The aims of the present study were two-fold: (i) to investigate the relationship between physical characteristics and the game statistics associated with ball-carrying capability amongst sub-elite rugby union players, and (ii) to predict the level of change in these physical characteristics required to improve the associated game statistic via regression analysis.